Modeling of acoustic emission signals in the case of cracks in the material - Бабак, В. П.; Філоненко, С. Ф.; Каліта, В. М. (Proceedings of National Aviation University, 2002)
The results of simulation of acoustic emission signals, which are formed in case of cracks in the material, are presented. Transformation of acoustic signal forms emission depending on conditions of development of cracks.